Prosopisinoxylon anciborae nov. gen. et sp. (Leguminosae, Mimosoideae) from the Late Miocene Chiquimil Formation (Santa María Group), Catamarca, Argentina - Martinez, Leandro Carlos Alcides (2010)
A new genus and species of fossil wood with Leguminosae (Mimosoideae) affinities from the Late Miocene Chiquimil Formation (Santa María Group) in Catamarca Province, Argentina, is described. Prosopisinoxylon anciborae Martínez lacks growth rings, is diffuse porous, has vessels of two distinct diameters, simple perforation plates, alternate and vestured intervessel pits, rays commonly 1 to 9 seriate and confluent axial parenchyma with prismatic crystals in chambered diffuse paratracheal parenchyma cells. This taxon has the greatest similarity to extant genus Prosopis L. Based on the presence of Prosopis fossil leaves and pollen in the Miocene San José and Morterito formations, Argentina, the genus expands its distribution in the past, showing that Prosopis was an important element of Miocene floras of northwestern Argentina and would explain its high extant diversity.